Acute localised exanthematous pustulosis induced by ceftriaxone: a case report on diagnostic challenges and treatment pitfalls - Draman, Samsul; Abd Rahman, Mohd Aizuddin; Wan Solahuddin, Wan Nurul Dhabitah; Hasnol Aidi, Aminuddin (Faculty of Medicine, UKM, 2026)
Acute localised exanthematous pustulosis (ALEP) is a rare variant of acute generalised exanthematous pustulosis (AGEP), characterised by the eruption of non-follicular, sterile pustules on an erythematous base following drug exposure. It is a benign drug reaction that manifests shortly after drug initiation and typically resolves within five to seven days after withdrawal of the offending agent. ALEP is frequently under recognised and may be mistaken for infectious pustular dermatoses. We report a case of a 20-year-old woman who developed multiple pruritic, painless pustular lesions over the chin and upper chest three days after starting intravenous ceftriaxone, which had been administered intraoperatively for a left hemilaminotomy and partial discectomy at L4/L5 and L5/S1. The lesions appeared on postoperative day two, without associated fever, and laboratory investigations revealed leukocytosis. A pustule swab grew Staphylococcus epidermidis, likely representing skin flora. She was initially diagnosed with folliculitis and treated with fucidic acid cream and oral Augmentin for five days, with apparent improvement at follow-up. A subsequent dermatology review noted complete resolution after ceftriaxone cessation. The absence of follicular involvement and rapid self-limited course, supported a diagnosis of ceftriaxone-induced ALEP despite the absence of histopathological confirmation. This case highlights the diagnostic challenges of distinguishing ALEP from postoperative infectious pustular eruptions, which may lead to unnecessary antibiotic use. Although rare, ceftriaxone-associated ALEP should be considered when acute pustular rashes occur shortly after drug initiation. Increased awareness among primary care and surgical clinicians is essential for appropriate recognition and management.